Faktor-faktor yang mempengaruhi volume pembiayaan berbasis bagi hasil dan rasio bopo pada perbankan syariah - WIRMAN WIRMAN (Jurnal Bisnis dan Akuntansi, 2017)
The objective of the study is to obtain empirical evidence of factors affecting the volume of financing based on cost sharing and the ratio of BOPO to Sharia Banking. The number of population in this study is the number of units analyzed consisting of all Islamic banks in Indonesia either BUS, UUS or BPRS. The method of selecting the sample used is purposive sampling. Testing using multiple regression analysis. The result of the research shows that there is influence of DPK to funding based on the result of mudharabah and musyarakah in both syariah banking institution in Indonesia. There is an effect of earnings on financing based on the sharing of mudharabah and musharaka in both Islamic banking institutions in Indonesia. There is no effect of NPF/non-performing financing on Mudharabah-based finance sharing in BUS in Indonesia. However, the NPF has a significant effect on mudharabah-based revenue sharing at the SRB. There is no effect of NPF / non-performing financing on the musharaka-based financing of the BUS in Indonesia. However, the NPF has a significant effect on the musharaka-based sharing financing in the SRB. There is no effect of interest rate on cost sharing based on mudharabah and musyarakah result in sharia banking in Indonesia. There is a funding effect based on the results of mudharabah and musyarakah on the ratio of BOPO in both Islamic banking institutions in Indonesia.